2012
DOI: 10.1143/apex.5.082101
|View full text |Cite
|
Sign up to set email alerts
|

AlGaN Deep-Ultraviolet Light-Emitting Diodes with External Quantum Efficiency above 10%

Abstract: Improvements of the internal quantum efficiency by reduction of the threading dislocation density and of the light extraction by using UV transparent p-type cladding and contact layers, UV reflecting ohmic contact, and chip encapsulation with optimized shape and refractive index allowed us to obtain the external quantum efficiency of 10.4% at 20 mA CW current with the output power up to 9.3 mW at 278 nm for AlGaN-based deep-ultraviolet light-emitting diodes grown on sapphire substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
294
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 443 publications
(299 citation statements)
references
References 7 publications
4
294
0
1
Order By: Relevance
“…[8][9][10] In AlN, the exciton binding energy is consistently reported to be around 53 meV; however, spin-exchange interaction has so far not been considered to interpret spectra, which leads to the situation that the identities of observed free exciton transitions are ambiguous.…”
mentioning
confidence: 99%
“…[8][9][10] In AlN, the exciton binding energy is consistently reported to be around 53 meV; however, spin-exchange interaction has so far not been considered to interpret spectra, which leads to the situation that the identities of observed free exciton transitions are ambiguous.…”
mentioning
confidence: 99%
“…However, the EQE decreases rapidly as the wavelength becomes shorter (by increasing the Al content in the Al x Ga 12x N). Although Shatalov et al 10 reported AlGaN DUV LEDs with an EQE above 10% at 278 nm, typical EQE values of commercial DUV LEDs are less than 5%. 1 The dominant reason for such a low EQE is the poor light-extraction efficiency (LEE) caused by the strongly anisotropic light emission that is mostly in a direction within the c-plane of Al x Ga 12x N. 1,8,9 The strongly anisotropic emission, called sidewall emission in this study, is due to the unique valence band (VB) structure of AlGaN at high Al contents (x.,0.25).…”
Section: Introductionmentioning
confidence: 99%
“…However, conventional LED chip geometries favor extracting light propagating parallel to the c-axis, and thus, the LEEs of AlGaN-based DUV LEDs with conventional chip geometries do not exceed 10%. 10,14,15 Conventional LEE-enhancing techniques-such as surface roughening, 16,17 substrate patterning 18 and incorporating anti-reflective coatings, 19 photonic crystals 20 and surface plasmonics 21 -are effective for GaInN-based visible LEDs but have a negligible effect on AlGaN DUV LEDs. 14 According to recent finite difference time domain calculations, the extraction of TM-polarized DUV light is .10 times lower than that of transverse electric (TE)-polarized light.…”
Section: Introductionmentioning
confidence: 99%
“…As a solution, light is most efficiently extracted from the substrate side of the devices using flip chip bonding. [2][3][4][5][6][7] To reduce internal reflection, micro-structure patterning has to be done on the back side of the devices, and device encapsulation and packaging is necessary. Despite these techniques, the achieved light extraction efficiency is only 25% 8 , which is much lower than the visible LEDs (> 80%) 9 .…”
mentioning
confidence: 99%
“…3,4,25 The absorbing p-type contact layer is an important reason that the light extraction efficiency of UV LEDs remains much lower than visible LEDs. 8,9 The tunneling injected UV LED structure mitigates the absorption loss issues in UV LEDs, since the InGaN interband tunneling layer used (< 4 nm) is significantly thinner than typical p-GaN capping layers (> 20 nm).…”
mentioning
confidence: 99%